Que profissão? Que trabalho? Trajetórias profissionais e construção identitária dos cientistas sociais egressos da UFSCar (1991-2021) - Silva, Érica Regina da (Universidade Federal de São Carlos, 2025)
The research object of this thesis is the l analysis of the professional insertion of undergraduates from the Social Sciences course at the Federal University of São Carlos (UFSCar) from the course's foundation in 1991 until the year 2021.It emphasizes the profession, professional identity, and the job market. The research starts from the question of how these social scientists position themselves professionally in contemporary society and where the current trends of the profession are heading. A mixed-methodological approach was adopted, including analysis of secondary data from DIGRA (Division of Academic Management and Records) and the administration of online questionnaires to graduates. The results point to the fragmentation of the professional identity of social scientists, marked by t multiple self-designations, and to the absence of a market reserve that ensures their specialized performance. It was found that, although there is an affective appreciation of the course, especially among those who continued on to graduate school, there is a mismatch between the training received and the demands of the market, especially outside the academic environment. Social recognition of the profession is limited, and the professional trajectories of graduates reflect instability, precariousness, and interprofessional disputes. The conditions for professionalization are influenced by variables such as gender, race, and social origin, whose effects were analyzed from an intersectional perspective. A difference was also observed between the symbolic value of education—associated with broadening one's worldview and forming values—and its limited practical application in the labor market. The study dialogues with the literature on the sociology of professions, highlighting the notions of hybrid and connective professionalism, and argues that social scientists face specific challenges in a context of reconfiguration of the world of work and the expansion of neoliberal rationality. Identification and disidentification are also analyzed based on the experiences reported by the graduates participating in the study. It is concluded that, although social sciences education has subjective and political meaning for graduates, it lacks more effective institutional strategies to expand concrete possibilities for professional integration and recognition.
What profession? What job? Professional trajectories and identity construction of social scientists graduating from UFSCar (1991-2021)
Keywords: Ciências sociais; Social sciences; Egressos universitários; Mercado de trabalho; Profissionalismo; Identidade profissional; University graduates; Job market; Professionalism; Professional identity; CIENCIAS HUMANAS::SOCIOLOGIA; 5. Igualdade de Gênero